Cleaning Pakistan?s Air: Policy Options to Address the Cost of Outdoor Air Pollution - Sánchez-Triana, Ernesto (World Bank, 2015)
The extent of urban air pollution in Pakistan?South Asia's most urbanized country?is among the world?s most severe, significantly damaging human health, quality of life, and the economy and environment of Pakistan. The harm from Pakistan's urban air pollution is among the highest in South Asia, exceeding several high-profile causes of mortality and morbidity in Pakistan.